U C Berkeley Heavy Reunion at Holiday Inn San Francisco - Watkins, Howard::::::::: (1981)
Frank Gumpert, Steve "Elmo" Rau with tambourine, David Morse with guitar, Carol Rau holding sheet music, and David Atkinson with guitar all singing